Creating PKWTT Contract and Irrelevant Company Regulations Refreshment of CV. XYZ in Accordance with the Labour Law - Risko Fitriano; Windi Afdal (ConCEPt - Conference on Community Engagement Project, 2022)
Companies are places for profit or profit, and every company is founded on alegal basis. In order for workers and prospective workers to understand existingcompany regulations, companies need to formulate company regulations andwork agreements, with company regulations and employment contracts,prospective workers and workers must comply with existing company rules,because company regulations are made based on existing facts or to minimizerisks that will occur in a company. Establishment of company regulations so thatwe can comply with existing regulations and comply with company SOPs. Thework agreement contains a binding agreement, in which the worker will work byreceiving a wage order from the employer, and contains the terms of work as wellas written and oral rights and obligations from both parties. The implementationof this community service uses an advocacy method to help partners (employers)improve their legal documents/agreements. The result of this community service isa draft PKWTT and a modernized draft of company regulations.